2022
DOI: 10.3389/fchem.2021.814647
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Sulfonamides in Aqueous Solution on Reusable Coconut-Shell Biochar Modified by Alkaline Activation and Magnetization

Abstract: Biochar is a low-cost adsorbent for sorptive removal of antibiotics from wastewater, but the adsorption efficiency needs to be improved. In this study, coconut-shell biochar was activated with KOH to improve the adsorption efficiency and magnetically modified with FeCl3 to enable recycling. The amount of KOH and the concentration of FeCl3 were optimized to reduce the pollution and production cost. The KOH-activated and FeCl3-magnetized biochar gave good sulfonamide antibiotic (SA) removal. The maximum adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…2(b)) was eroded to form a rough porous structure, the CO, CO 2 , and other gases produced at high temperatures were lost through the pores, which resulted in the formation of micropores on the MBC surface. 31 Furthermore, the FMBC (Fig. 2(c)) showed a more irregular, uneven, and pore-developed surface morphology aer loading with Fe/Co metals, and the number of micropores on the surface increased substantially.…”
Section: Resultsmentioning
confidence: 96%
“…2(b)) was eroded to form a rough porous structure, the CO, CO 2 , and other gases produced at high temperatures were lost through the pores, which resulted in the formation of micropores on the MBC surface. 31 Furthermore, the FMBC (Fig. 2(c)) showed a more irregular, uneven, and pore-developed surface morphology aer loading with Fe/Co metals, and the number of micropores on the surface increased substantially.…”
Section: Resultsmentioning
confidence: 96%
“…The pH of the solutions during sorption experiments has to be considered [ 49 ], and in this work, they ranged between 7.6 and 7.8, indicating that SFA is present mostly as a neutral molecule. Hydrophobic interactions dominated by the higher C content of BC-Fe ( Table 1 ) would be mainly responsible for this increase in sorption rather than the pH, together with the formation of charge-assisted H-bonds [ 11 , 50 , 51 , 52 ]. Since an increase in sorption was observed upon activation without great variations in the specific surface area values, this increase can be attributed to the microsite modifications on BC’s surface in BC-Fe and the changes in the texture as observed from SEM micrographs ( Figure 1 ) and data from Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This situation has stimulated the development of economical and effective mitigation methods for antibiotic removal from the environment [ 11 , 12 ]. Therefore, the sorption and persistence of sulfonamides need to be assessed since these are key factors determining their adverse impact [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Step Temperature (time lasted) [56] The satellite peak located at 288.8 eV, which is attributed to π-π stacking, indicated graphite structures in TBI K (Figure 4A H groups, respectively. [57] Meanwhile, the intensity of the peak was very small at a binding energy of 533.1 eV, which indicated that the O-H content in TBT K is quite low (Figure 4E).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4A, the peaks of the C 1s spectra are located at 284.6, 285.6, and 286.5 eV, which correspond to C = C, C‐O, and C = O functional groups, respectively. [ 56 ] The satellite peak located at 288.8 eV, which is attributed to π‐π stacking, indicated graphite structures in TBI K (Figure 4A and D). The O 1s spectra of TBI K and TBT K are shown in Figure 4B and E, respectively.…”
Section: Discussionmentioning
confidence: 99%